Characteristics of Primary Health Care Facilities (FKTP) That Influence the Adoption of Online Appointment Scheduling via the National Health Insurance Mobile App (MJKN) in Blitar and Nganjuk Regencies - Salsabiila Tita Fauziyah; Yuly Peristiowati; Ratna Wardani; Atik Setiawan; Novita Ana Anggraini (Lembaga Teewan Journal Solutions, 2026)
The National Health Insurance (Jaminan Kesehatan Nasional/JKN) program administered by BPJS Kesehatan has covered 278.1 million participants, representing 98.45% of Indonesia’s population. The increasing number of participants has consequently led to longer waiting times at primary healthcare facilities (Fasilitas Kesehatan Tingkat Pertama/FKTP). To address this issue, BPJS Kesehatan introduced the online queue feature through the Mobile JKN (MJKN) application in 2018. However, the utilization rate of the online queue system in Blitar Regency (10.65%) and Nganjuk Regency (12.28%) remains below the national target of 18%. This study aimed to analyze the influence of FKTP facility characteristics, including ownership status, facility type, and service type, on the adoption of the MJKN online queue system in Blitar and Nganjuk Regencies. This study employed a quantitative approach with a cross-sectional design. The population consisted of 133 FKTP, of which 103 facilities were selected using proportional random sampling. Secondary data were obtained from the Health Facilities Information System (HFIS) and the BPJS Kesehatan Business Intelligence Dashboard. Data were analyzed using binary logistic regression. The results showed that the type of FKTP significantly influenced the utilization of the MJKN online queue system (p=0.044; OR=14.786). In contrast, FKTP ownership (p=0.396; OR=3.702) and service type (p=0.550; OR=1.966) did not significantly affect online queue utilization. In conclusion, the type of FKTP plays a significant role in determining the achievement of MJKN online queue utilization, whereas ownership and service type do not. Therefore, FKTP and BPJS Kesehatan should formulate targeted strategies and prioritize optimization efforts based on FKTP characteristics to improve the adoption of the MJKN online queue system. Further studies are also recommended to examine individual-level determinants among MJKN application users.